Implementasi UU No. 6 Tahun 2014 terhadap Bantuan Langsung Tunai di Desa Gelora, Kecamatan Sikur, Kabupaten Lombok Timur - Sopian, Andri (Melati Institute, 2025)
This research analyzes the implementation of Law No. 6/2014 on Villages, with a focus on the Village Fund Direct Cash Transfer (BLT) program in Gelora Village, Sikur Sub-district, East Lombok District, West Nusa Tenggara. This law provides a legal framework for villages to manage their finances, including funds for social assistance programs such as BLT, supported by government regulations, relevant ministerial regulations, and East Lombok Regent regulations that regulate the allocation, amount, and criteria for BLT recipients. This study examines the BLT implementation mechanism in Gelora Village, where the majority of the population earns a living in the agricultural sector, and evaluates its impact on community welfare and village development. The implementation in Gelora Village showed initial challenges related to transparency that triggered community protests, but later received an award from the Ministry of Villages for the successful distribution in 2020. The program is considered to have contributed to meeting the basic needs and purchasing power of the community, although potential negative impacts such as social jealousy were also identified. The main challenges faced include transparency issues, accuracy of recipient data, potential misuse of funds (referring to PKH cases in the same region), and inter-agency coordination. This research recommends increased transparency and accountability, strengthened data validation, better program socialization, strict supervision, improved coordination, and continuous impact evaluation to optimize the effectiveness of the BLT program as mandated by the Village Law.